Cardiotoxicity of Antineoplastic Therapies and Applications of Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Mo-Fan Huang; Lon Kai Pang; Yi-Hung Chen; Ruiying Zhao; Dung-Fang Lee (Cells, 2021)
The therapeutic landscape for the treatment of cancer has evolved significantly in recent decades, aided by the development of effective oncology drugs. However, many cancer drugs are often poorly tolerated by the body and in particular the cardiovascular system, causing adverse and sometimes fatal side effects that negate the chemotherapeutic benefits. The prevalence and severity of chemotherapy-induced cardiotoxicity warrants a deeper investigation of the mechanisms and implicating factors in this phenomenon, and a consolidation of scientific efforts to develop mitigating strategies. Aiding these efforts is the emergence of induced pluripotent stem cells (iPSCs) in recent years, which has allowed for the generation of iPSC-derived cardiomyocytes (iPSC-CMs): a human-based, patient-derived, and genetically variable platform that can be applied to the study of chemotherapy-induced cardiotoxicity and beyond. After surveying chemotherapy-induced cardiotoxicity and the associated chemotherapeutic agents, we discuss the use of iPSC-CMs in cardiotoxicity modeling, drug screening, and other potential applications. Improvements to the iPSC-CM platform, such as the development of more adult-like cardiomyocytes and ongoing advances in biotechnology, will only enhance the utility of iPSC-CMs in both basic science and clinical applications.